Stability in distribution of Markov-modulated stochastic differential delay equations with reflection. Issue 3 (2nd July 2016) - Bo, Lijun; Yuan, Chenggui
ABSTRACT: In this paper, we discuss Markov-modulated stochastic differential delay equations with reflection. The aim of this paper is to extend the stability criterion in distribution as in [Systems and Control Letters Vol 50 (2003) 195–207] to the equations with reflection. Interesting examples are provided to demonstrate not only our theory, but also the importance of Markov-modulating.